Light Manufacturing in Vietnam : Creating Jobs and Prosperity in a Middle-Income Economy - Dinh, Hinh T. (Washington, DC: World Bank, 2014)
Light Manufacturing in Vietnam makes the case that, if the country is to continue along a rapid economic growth path and create jobs, it must undertake a structural transformation that can lift workers from low-productivity agriculture and the mere assembly of imported inputs to higher-productivity activities. Vietnam needs to address fundamental issues in the manufacturing sector that, until now, have been masked by economic growth. The book shows that there is a dichotomy between domestic enterprises and enterprises supported by foreign direct investment. The dominant state-owned enterprises and foreign-invested firms are often not integrated with smaller, domestic firms through backward or forward links in the use of domestically produced inputs or intermediate products. Growth in the domestic light manufacturing sector has arisen from the sheer number of micro and small enterprises rather than from expansion in the number of medium and large firms. As a consequence, final products have little value added; technology and expertise are not shared; and the economy has failed to move up the structural transformation ladder. This structure of production is one of the reasons Vietnam's rapid process of industrialization over the last three decades has not been accompanied by a favorable trade balance.